Internationally Administered Territories - International Protectorates? : an Analysis of Sovereignty over Internationally Administered Territories with Special Reference to the Legal Status of Post-War Kosovo. - Smyrek, Daniel Sven (Tübinger Schriften zum internationalen und europäischen Recht - Band 80., 2011)
Hauptbeschreibung The author begins his survey by offering the reader an overview of the concepts of ""physical control over a territory"""" and ""territorial sovereignty"""". He then moves on to examine different scenarios in which territories have been administered by an organ representing the international community and explains how the issue of sovereignty was dealt with in each of these cases. In this context, the author offers a fascinating review of the recent case of Kosovo under UN administration describing the intricacies associated therewith. After thoroughly examining both t.